Graphic analysis of flow-volume curves: a pilot study - Lee, Jungsil; Lee, Choon-Taek; Lee, Jae Ho; Cho, Young-Jae; Park, Jong Sun; Oh, Yeon-Mok; Lee, Sang-Do; Yoon, Ho Il (BMC pulmonary medicine, 2016)
Background Conventional spirometric parameters have shown poor correlation with symptoms and health status of chronic obstructive pulmonary disease (COPD). While it is well-known that the pattern of the expiratory flow-volume curve (EFVC) represents ventilatory dysfunction, little attempts have been made to derive quantitative parameters by analyzing the curve. In this study, we aimed to derive useful parameters from EFVC via graphic analysis and tried to validate them in patients with COPD. Methods Using Graphical Analysis 3.4 Vernier Software, we derived from the EFVC such parameters as area of obstruction (Ao), area of triangle (AT), area of rectangle (AR) and ratio of volume at 75 and 25 % peak expiratory flow (PEF) (0.25/0.75 V). For validation, we reviewed clinical and spirometric data of 61 COPD patients from Seoul National University Airway Registry (SNUAR) and Korean obstructive Lung Disease (KOLD) cohorts. Results Of all parameters, only RV/TLC significantly correlated with scores from St. George’s Respiratory Questionnaire (SGRQ) (r = 0.447, p = 0.037). Six-minute walking distance (6MWD) highly correlated with Ao/AR (r = −0.618, p = 0.005) and Ao/PEF (r = −0.581, p = 0.009) whereas neither FEV 1 nor FEV 1 /FVC had significant correlation with 6MWD. Conclusions Ao/AR and Ao/PEF are promising parameters which correlate well with the exercising capacity of COPD patients.